1996
DOI: 10.1159/000211438
|View full text |Cite
|
Sign up to set email alerts
|

No Effect of Albumin on the Dermal Absorption Rate of Hydrocortisone 21-Butyrate, Permethrin or Diflunisal in the Isolated, Single-Pass Perfused Rabbit Ear

Abstract: Rabbit ears were single-pass perfused with a buffer solution containing either 6% hetastarch or 5% bovine serum albumin. Hydrocortisone 21-butyrate (5 mM), diflunisal (17 mM) or permethrin (33 mM) was added to isopropyl myristate with 5% polyethylene, and applied to about 40% of the epithelial surface area of the ear. Hydrocortisone 21-butyrate or permethrin were not found in the effluent with hetastarch or albumin. Following cutaneous ester hydrolysis, the appearance rate of hydrocortisone was about 4 pmol/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The effects of receptor fluid on penetration are well researched for lipophilic compounds. DeLange et al (1994) showed that penetration of xylene in a perfused pig ear organ model was dependent on the protein content of the receptor fluid, though the influence of the receptor fluid depended on the penetrating compound (Bast and Kampffmeyer 1996;Pelling et al 1998). It is unexpected, however, to find such an effect for relatively hydrophilic compounds such as EE and BE.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of receptor fluid on penetration are well researched for lipophilic compounds. DeLange et al (1994) showed that penetration of xylene in a perfused pig ear organ model was dependent on the protein content of the receptor fluid, though the influence of the receptor fluid depended on the penetrating compound (Bast and Kampffmeyer 1996;Pelling et al 1998). It is unexpected, however, to find such an effect for relatively hydrophilic compounds such as EE and BE.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments with 5% BSA in the perfusion fluid [1] the absorption of hydrocortisone 21-butyrate, permethrin, or diflunisal was not enhanced compared with 6% hetastarch. In the present experiments with retinoids, however, we only detected percutaneous absorption in the presence of BSA.…”
Section: Discussionmentioning
confidence: 70%
“…The highest application density of these impurities, concomitant with the substrate, and their percutaneous absorption rates have led the calculated appearance rates of these impurities to be 6 five times below the detection limit. The origin of all the other substances has been described elsewhere [1,5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procaine and hydrocortisone 21-hemisuccinate are ionized at physiological pH and so are more soluble in the perfusion buffer. This might also apply to diflunisal and 3-phenoxybenzoic acid which reached high steady-state absorption rates (1600 pmol/min per cml 11 and 600 pmol/min per cm2 12 respectively, normalized for 10 mM substrate concentration in isopropyl myristate) although we did not look for their metabolites.…”
Section: Introductionmentioning
confidence: 99%